Institutional Divergence within the Ministry of Religious Affairs: Responses to the Establishment Plan of a State Confucian College - Herza; M. Aries Taufiq; Izcha Pricispa; Nur Faizza Tunnisa (Loquēla (Journal of Linguistics, Literature, and Education), 2026)
The establishment of the Confucian State College of Indonesia (SETIAKIN) in the Bangka Belitung Islands Province was initiated by the Ministry of Religious Affairs (MoRA) in 2019 to expand access to higher religious education for the Confucian community. The policy generated considerable controversy, particularly among conservative Islamic groups concerned about its potential impact on religious identity and social harmony. This study examines institutional divergence among actors within the Provincial and Central Bangka offices of MoRA in responding to the proposed institution. Employing an exploratory-descriptive qualitative approach, data were collected through interviews, observation, and document analysis. Drawing on Michel Foucault’s concepts of discourse, power/knowledge, and governmentality, the findings reveal that divergent responses emerged from competing governmental rationalities and discursive constructions of social reality. Although several actors initially opposed the project, their positions gradually shifted toward compliance following the central ministry’s reaffirmation of the policy. The study argues that this shift reflected bureaucratic adaptation rather than ideological transformation, highlighting how religious policy implementation is shaped by contesting discourses within state institutions.